Hollow magnetic molecularly imprinted polymer based on metal‐organic framework for capture of ciprofloxacin. Issue 8 (17th May 2022) - Zhou, Shu; Fu, Jinli; Zhao, Pengfei; Tang, Sisi; Wu, Xiaodan; Yang, Zhaoxia; Zhang, Zhaohui
Abstract: The development of a simple and rapid separation and analysis method with high selectivity toward ciprofloxacin is of great importance for environmental protection. Herein, this paper reported a hollow magnetic zeolitic imidazolate framework‐67 based molecularly imprinted polymer for selective adsorption and enrichment of ciprofloxacin. The morphology and structural properties of the hollow magnetic molecularly imprinted polymer were characterized by scanning electron microscopy, transmission electron microscopy, infrared spectroscopy, and thermogravimetry, and the results showed that the material has an obvious hollow structure, good thermal stability, and magnetic properties. The hollow magnetic imprinted polymer has a higher adsorption capacity (75.59 mg/g) and shorter adsorption saturation time (50 min) toward ciprofloxacin. Moreover, the hollow magnetic molecularly imprinted polymer showed excellent adsorption ability, stability, and repeatability. The hollow magnetic imprinted polymer was used to detect trace ciprofloxacin in actual samples (river water, human urine, chicken) successfully with the recoveries of 91.4–100.4%. With the advantages of high recovery (91.4–100.4%), high speed (50 min), and high selectivity (selectivity factor > 2.50), the hollow magnetic molecularly imprinted polymer has broad application prospects in the efficient adsorption of ciprofloxacin.